An examination of the relationships between customer relationship management quality, service quality, customer satisfaction and customer loyalty: The case of five star hotels - Mokhtar, Susiana; Sjahruddin, Herman (Advances in Social Sciences Research Journal, 2019)
Customer’s loyalty seems to have received a lot of attention from scholars. This research began by describing customer relationship management (CRM) quality and service quality. The meditational model that links CRM quality and service quality with customer loyalty through customer satisfaction is proposed. Appropriate steps are identified and surveys conducted among 1,825 hotel customers using simple random sampling techniques. 773 questionnaires were returned with a response rate of around 42.3 percent, 46 questionnaires were deemed unusable because of the large amount of missing data so that 309 analysis units could be used. The results show that customer satisfaction plays a mediating role in the effect of CRM quality and service quality on customer loyalty. The implications are discussed, the limitations of the study are noted and the possible fields for further research are shown.